Mixed matrix membrane microextraction for the analysis of polycyclic aromatic hydrocarbons, non-steroidal anti- inflammatory drugs and tobramycin in solutions - Mukhtar, Nurul Hazirah (2018)
New approaches in miniaturised sample preparation have been investigated. In this study, novel microextraction methods based on the use of a mixed matrix membrane (MMM) were developed in various designs and applications. The potential for carbonaceous nanomaterials to be used as adsorbents for the MMM microextraction and preconcentration of organic pollutants was demonstrated. In this method, multiwall carbon nanotubes (MWCNT) and single layer graphene (SLG) nanoparticles were individually incorporated through dispersion in a cellulose triacetate (CTA) polymer matrix to form MWCNT-MMM and SLG-MMM, respectively. The prepared membranes were evaluated for the extraction of selected polycyclic aromatic hydrocarbons (PAHs) from sewage pond water samples. The extraction was performed by dipping a small piece of membrane (7 mm × 7 mm) in a stirred 7.5 mL sample solution to initiate the analyte adsorption. Enrichment factors of 54 to 100 were achieved with relative recoveries of 99% to 101%. The developed method proved a simple, feasible, and cost-effective microextraction technique. A new sample pre-treatment technique termed mixed matrix membrane tip extraction (MMMTE) has been developed and combined with high performance liquid chromatography (HPLC) for the determination of selected non-steroidal antiinflammatory drugs, namely sulindac, indoprofen, naproxen, diclofenac and ibuprofen in environmental water samples. The extraction was carried out by preparing a thin film mixed matrix membrane with immobilised C18 adsorbents on a 100 µL tip wall. The microextraction was conducted by continuously flowing the sample solution through the membrane tip device for the effective analyte adsorption process. This step was followed by desorption of the analyte into a small amount of organic solvent prior to HPLC analysis. The detection limits of the method for the selected drugs were in the range of 10-50 pg/mL. Enrichment factors of up to 249 fold were achieved with relative recoveries of > 90%. A novel mixed matrix membrane tip extraction using hydrophilic lipophilic balance particles was developed for the preconcentration of the aminoglycoside antibiotic from the human plasma prior to the capillary electrophoresis with a contactless conductivity detection (CEC 4D). The parameters affecting the extraction efficiency such as the dynamic rinse time and desorption solvent were investigated in detail. Under the optimised conditions, the limit of detection and the limit of quantification of the method for tobramycin are 0.01 and 0.03 µg/mL, respectively. Relative recoveries in spiked human plasma were in the range of 99.6-99.9% with relative standard deviations between 3.6% and 8.7%.